Comparing the acute cardiac autonomic response to home and away games in collegiate female volleyball players - Edmonds, R.; Dzandzara, A.; Siedlik, J. (The Journal of Strength and Conditioning Research, 2021)
Heart rate (HR) variability (HRV) is a well-documented tool used within athletic populations to identify an athlete's potential readiness to compete. As a measure of cardiac autonomic function, it may also allow insight into documenting how athletes respond to the physiological demands of travel during the collegiate season. Purpose: To document the acute cardiac autonomic response of female collegiate volleyball players when competing at home or away. Methods: A 55-second HRV measurement was recorded each morning upon awakening, using a smartphone application and a pulse-wave finger sensor. These measurements were taken each day throughout the collegiate volleyball season. Athletes self-reported measures (ASRM) were also recorded daily after completing the HR recording. Subjective measures of sleep, fatigue, muscle soreness, stress, and mood were recorded on a 1-10 scale. Data normality was assessed using a Shapiro-Wilk test of normality. A Kruskal-Wallis one-way analysis of variance was used to examine differences between game number (game 5-34), location (home vs. away), and day (pre-game, game day, post-game) for all dependent variables. Data is presented as (mean ± standard deviation). Results: No significant differences (p > 0.05) in HR or HRV were observed between home versus away games. Likewise, HR and HRV were similar at pre-game, gameday, and post-game recordings. Athlete self-reported measures of sleep, muscle soreness, stress, and mood were all similar (p > 0.05) when comparing home versus away game, and pre-game, gameday, and post-game recordings. However, subjective measures of fatigue were significantly higher (p < 0.05) post-game (5.5 ± 1.6) when compared against pre-game (5.9 ± 1.3), and gameday (5.9 ± 1.4) measures. Interestingly, subjective measures of fatigue were also significantly higher (p< 0.05) for home games (6.0 ± 1.4) compared to away games (5.5 ± 1.4). Conclusions: The physiological demands of domestic travel associated with collegiate volleyball do not appear to influence HRV. Surprisingly, cardiac autonomic function was similar the morning after a game and game day, suggesting this cohort of collegiate athletes were able to tolerate the physiological demands competition appropriately. Lastly, of particular interest was that athletes reported elevated levels of fatigue during home games when compared to games played away. Practical Applications: Understanding how athletes cope with the physiological and psychological demands of travel in season, may allow coaches and sports scientists to enhance athlete management and workload, and as such maximize favorable training and game performance. Furthermore, recognizing the additional demands placed on collegiate athletes when competing at home may influence their perceived level of fatigue allows coaches to better prepare athletes physically and mentally prior to competition.